2006
DOI: 10.1029/2005jd006006
|View full text |Cite
|
Sign up to set email alerts
|

Role of convection in global‐scale transport in the troposphere

Abstract: The role of convection in global‐scale transport in the troposphere is studied by using climatological Green's functions of the mass conservation equation for a conserved, passive tracer. The Green's functions are calculated from long‐term atmospheric trajectory calculations based on three‐dimensional winds from a 19‐year simulation by Version 3 of the NCAR Community Climate Model (CCM3). Two trajectory calculations are compared: one that includes the effects of the model's parameterized convection and one tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…However, the resemblance of our results to the seasonal cycle of effective diffusivity in observations (e.g., Haynes and Shuckburgh 2000b) indicates that our results can hold qualitatively even in the presence of moisture. This is consistent with the results that globalscale tracer transport in the model simulations with and without convective transport are qualitatively similar (Erukhimova and Bowman 2006;Hess 2005).…”
Section: Conclusion and Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the resemblance of our results to the seasonal cycle of effective diffusivity in observations (e.g., Haynes and Shuckburgh 2000b) indicates that our results can hold qualitatively even in the presence of moisture. This is consistent with the results that globalscale tracer transport in the model simulations with and without convective transport are qualitatively similar (Erukhimova and Bowman 2006;Hess 2005).…”
Section: Conclusion and Discussionsupporting
confidence: 81%
“…Using a Green's function diagnostic, Bowman and collaborators (Bowman and Carrie 2002;Bowman and Erukhimova 2004;Erukhimova and Bowman 2006) concluded that tropospheric transport can be described qualitatively by the slow mean diabatic circulation and rapid isentropic mixing. In the observations, the mean diabatic circulation exhibits an equator-to-pole cell, with poleward circulations in the stratosphere and in the upper troposphere and an equatorward return flow near the surface (e.g., Tanaka et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics, the probability distribution functions of column water vapor and trace gases of different chemical sources/sinks exhibit similar exponential tails, providing observational evidence of tropical convection's influence on tracer distributions [ Neelin et al , ; Lintner et al , ]. Chemical transport models also show that convection can enhance vertical and horizontal tracer transport [e.g., Gilliland and Hartley , ; Hess , ; Erukhimova and Bowman , ] and that interhemispheric transport is modulated by the seasonal migration of the Hadley circulation [ Bowman and Cohen , ]. Meanwhile, the Asian monsoon anticyclone is associated with horizontal eddy shedding and irreversible mixing of trace gases along its southward edge [ Popovic and Plumb , ], and upper tropospheric Rossby wave breaking is very efficient at mixing air masses across the equator [ Waugh et al , ].…”
Section: Introductionmentioning
confidence: 99%
“… Bowman and Carrie [2002] also indicated the existence of a subtropical mixing barrier, but suggested a barrier‐free region around the equator. Consequently, the subtropical transport barrier divides the global troposphere into three parts, namely, the tropics, NH extratropics, and SH extratropics, distinctly affecting the latitudinal tracer variations [e.g., Plumb and Mahlman , 1987; Erukhimova and Bowman , 2006].…”
Section: Introductionmentioning
confidence: 99%